2023
DOI: 10.1136/bmjdrc-2023-003649
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variant rs9939609 inFTOis associated with body composition and obesity risk in Korean females

Hyeon-Gyo Park,
Jeong-Hwa Choi

Abstract: IntroductionThe fat mass and obesity-associated (FTO) gene is a significant locus in obesity. However, the association betweenFTOgenetic variants and body composition has not been fully elucidated.Research design and methodsThis observational study examined the associations ofFTOrs9939609 T>A with obesity and body composition markers in Koreans. A total of 6474 participants from the Korean Genome and Epidemiology Study were analyzed for their general characteristics, body composition andFTOgenotype with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…A meta-analysis performed by Zhao et al identified a strong association between FTO SNPs and obesity risk in the Chinese population (OR 1.30; 95% CI: 1.19-1.42, P < 0.0001) [22]. Park and Choi showed that FTO rs9939609 is associated with obesity risk in Korean women [23]. A study conducted by Perez-Luque et al on the Mexican population found that rs9939609, rs9930506, and rs1421085 are key to gaining weight after bariatric surgery [24].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis performed by Zhao et al identified a strong association between FTO SNPs and obesity risk in the Chinese population (OR 1.30; 95% CI: 1.19-1.42, P < 0.0001) [22]. Park and Choi showed that FTO rs9939609 is associated with obesity risk in Korean women [23]. A study conducted by Perez-Luque et al on the Mexican population found that rs9939609, rs9930506, and rs1421085 are key to gaining weight after bariatric surgery [24].…”
Section: Discussionmentioning
confidence: 99%
“…An often studied SNP is rs9939609homozygous for this variant in adults has a 1.67-fold increased risk of obesity [107]. Park and Choi found this dependence, especially in women [108]. Studies demonstrate that FTO SNPs may also be associated with lean mass index (LMI) and sarcopenia [109].…”
Section: Genetic Susceptibility To Sarcopenic Obesitymentioning
confidence: 99%